2014
DOI: 10.1080/13596748.2014.955374
|View full text |Cite
|
Sign up to set email alerts
|

A comparative thematic review of vocational leadership literature from the USA, Great Britain and Australia

Abstract: Vocational education and its leadership is an important sphere of economic activity worldwide and is being impacted by several trends including: the increasing significance and centrality of skills development in today's economies; economic trends associated with globalisation (internationalisation of education and emergence of global labour markets); and demographic trends resulting in ageing populations and workforces. Leadership in vocational education contexts is crucial to the economic success of this sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 136 publications
0
6
0
Order By: Relevance
“…While systems and structures vary dependant on country, the education and training of the international workforce to possess technical skills and knowledge to operate effectively in the workplace are paralleled. As highlighted by Crossman and Cameron (2014), the contribution of FE to the global economy is significant, and therefore, it is important to gain a better understanding of how it is administered.…”
Section: Introductionmentioning
confidence: 99%
“…While systems and structures vary dependant on country, the education and training of the international workforce to possess technical skills and knowledge to operate effectively in the workplace are paralleled. As highlighted by Crossman and Cameron (2014), the contribution of FE to the global economy is significant, and therefore, it is important to gain a better understanding of how it is administered.…”
Section: Introductionmentioning
confidence: 99%
“…I use the proportional allocation approach to calculate the scale of strata. According to Creswell (2012), this makes for a high percentage of inclusion in the overall population. Four hundred ninety-one students and 285 teachers, representing 89.1 percent and 89 percent of the targeted survey, were gathered in relevant questionnaires.…”
Section: Population and Samplingmentioning
confidence: 99%
“…• technical and further education institutes in Australia (Adams and Gamage 2008) • further education institutes (Drodge 2002) and statutory universities (Smith 2002) in Great Britain • community colleges in the USA (Crossman and Cameron 2014) • middelbaar beroepsonderwijs (MBO) and hoger beroepsonderwijs (HBO) institutes in the Netherlands • Berufsschulen and Fachhochschulen in German speaking countries VPE institutes need to be responsive to changes in society and industry. In western Canada these changes include increasingly diverse student populations and frequently changing industry standards (Darwin 2007;Harris et al 2001).…”
Section: Vocational and Professional Education In Canadamentioning
confidence: 99%
“…Not only is there a lack of preparation for department chairs as educational leaders, there also seems to be little substantive knowledge base regarding leadership for learning in VPE (Burke 2014). In fact, much of the literature on leadership in post-secondary contexts draws heavily on business literature, which focuses on overall roles and responsibilities and rarely gives serious consideration to issues of teaching and learning (Basham and Campbell 2010;Crossman and Cameron 2014;Smith 2002). In the context of VPE specifically, Adams and Gamage (2008) identified the need for leaders to focus on the educational dimension of their work and suggested that the shift to managerial responsibilities is having an effect on leaders' abilities to ensure quality educational programming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation